Computational predictions of corroles as a class of Hsp90 inhibitors1. Issue 11 (13th November 2015) - Teo, Ruijie D.; Dong, Sijia S.; Gross, Zeev; Gray, Harry B.; Goddard, William A.
<x xml:space="preserve">Abstract</x> We predict corroles as a promising class of Hsp90 inhibitors by applying docking studies and molecular dynamics simulations.